1998
DOI: 10.1128/jvi.72.4.3196-3204.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Bovine Leukemia Virus Encapsidation Signal Is Composed of RNA Secondary Structures

Abstract: The encapsidation signal of bovine leukemia virus (BLV) was previously shown by deletion analysis to be discontinuous and to extend into the 5′ end of the gag gene (L. Mansky et al., J. Virol. 69:3282–3289, 1995). The global minimum-energy optimal folding for the entire BLV RNA, including the previously mapped primary and secondary encapsidation signal regions, was analyzed. Two stable stem-loop structures (located just downstream of the gagstart codon) were predicted within the primary signal region, and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Packaging efficiency of L-R1-derived sequences. There is experimental evidence supporting the idea that genome packaging in some RNA viruses depends on the secondary structure of the PS (8,30,31). It has been shown that the L-R1 sequence was responsible for packaging in TGEV.…”
Section: Delimitation Of Tgev Genome Sequences Required For Defectivementioning
confidence: 87%
See 1 more Smart Citation
“…Packaging efficiency of L-R1-derived sequences. There is experimental evidence supporting the idea that genome packaging in some RNA viruses depends on the secondary structure of the PS (8,30,31). It has been shown that the L-R1 sequence was responsible for packaging in TGEV.…”
Section: Delimitation Of Tgev Genome Sequences Required For Defectivementioning
confidence: 87%
“…The continuity between the leader sequence (nt 1 to 99) and downstream sequences (nt 100 to 598) in the PS was required for packaging, since the insertion of ectopic viral sequences between the leader and R1 in sgmRNA L-3a-R1 led to a significant reduction in the packaging efficiency compared to that of sgmRNA L-R1. This continuity might be required to maintain the correct secondary structure of the PS, since structural requirements frequently determine packaging in RNA viruses (8,30,31). Further deletions along the TGEV PS prevented packaging of viral RNAs, indicating that the whole genomic region was necessary for its function.…”
Section: Discussionmentioning
confidence: 99%
“…Its relentless ability to mutate arises from a high mismatch error rate (10 À3 to 10 À5 nucleotide bases per cycle) of the viruss reverse transcriptase enzyme and the absence of exonuclease-based proofreading activity. [24,25] These factors, in conjunction with the viruss rapid replication cycle (10 10 virions per day) and genetic recombination ability, result in seemingly endless genetic diversification. [26,27] However, the number of variants within the quasi-species at a given time is limited by natural selection, deleterious mutations, and limited host cell availability, and by inactivation from the hosts immune system response.…”
Section: Mechanism Of Drug Resistancementioning
confidence: 99%
“…To examine whether HTLV-1 MA and NC play similar roles as the analogous proteins in HTLV-2, fluorescence anisotropy (FA) binding assays were performed using fluorescently labeled RNAs derived from the previously proposed HTLV-1 ⌿ element (SL(450 -470), SL(474 -508), and SL(447-512) in Fig. 1A) (11,12). HTLV-1 SL(450 -470) and SL(474 -508) RNA sequences derived from a provirus cloned from the lymphocytic cell line CS-1 were previously used to replace BLV SL1 and SL2 individually and simultaneously.…”
Section: Htlv-1 Ma But Not Nc Binds To Putative Packaging Signal Stmentioning
confidence: 99%
“…downstream of the gag start codon and consists of two stemloop (SL) elements (10,11). Replacement of the BLV packaging signal with a similar region from either HTLV-1 or HTLV-2 led to only partial BLV replication defects, suggesting some level of conservation in the function of deltaretroviral packaging signals (11,12).…”
mentioning
confidence: 99%